Carbon Dioxide Absorption in a Fabricated Wetted-Wall Column Using Varying Concentrations of Aqueous Ammonia - H. E. E. Ching; L. M.P. Co; S. I. C. Tan; S. A. Roces; N. P. Dugos; J. Robles; M. M. Uy (ASEAN Journal of Chemical Engineering, 2013)
Due to the continued increasing levels of CO2 emissions that is contributing to climate change, CO2 mitigation technologies, particularly carbon capture and storage, are being developed to address the goal of abating CO2 levels. Carbon capture technologies can be applied at the pre-combustion, oxy-fuel combustion, and post-combustion stages, the latter being the most widely used due to its flexibility. Among the several CO2 separation processes available for carbon capture, absorption is the most widely used where amine solutions are used as absorbents. This paper highlights the use of a wetted wall column fabricated by Siy and Villanueva (2012) and simulated flue gas to determine the performance of CO2 absorption in terms of the percentage of CO2 absorbed, the steady state time, and the overall gas mass transfer coefficient. The concentrations used were 1, 5, 10, and 15% NH3(aq) at a constant temperature range of 12-17ºC, solvent flow rate of 100 mL/min, and simulated flue gas flow rate of 2 L/min. It was found that increasing the solvent concentration resulted in a proportional increase both in the percentage of CO2 absorbed and the overall gas mass transfer coefficient. The average percentage of CO2 absorbed ranged within 52.25% to 95.29% while the overall mass transfer coefficient ranged from 0.1843 to 0.7746 mmol/m2∙s∙kPa. However, erratic behavior was seen for the time required for the system to reach steady state. Using Design ExpertTM for analysis, the results showed that the effect of varying the concentration had a significant effect on the percentage of CO2 absorbed and the overall gas mass transfer coefficient. The results proved that the greater the aqueous ammonia concentration, the greater the percentage of CO2 absorbed. The range of 5-10% aqueous ammonia is recommended because the percentage of CO2 absorbed peaks at an average of 92% beyond the range of 5-10%.